Library and Social Media Use as Predictors of National Integration among Distance Learning Students in Benin Study Center, Nigeria - Igbinovia, Magnus Osahon; Ambrose, Smart E.; Solanke, Esther Oluwayinka (The International information & library review, 2018)
The study seeks to investigate library and social media use as predictors of national integration among distance learning students in Benin Study Center, Nigeria, using four research questions and four null hypotheses. The survey research design of the correlation type was employed for a population of 18,000 undergraduate students, while the Israel (1992) model supported the use of 200 undergraduates as the sample size for the study. The questionnaire pretested to yield reliability of 0.86 Cronbach alpha elicited data for the study analyzed using descriptive and inferential statistics. The results were presented, discussed, and recommendations were made based on the study's conclusion.